2021
DOI: 10.3389/fphys.2021.665821
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Hypoxia and Brain Function in Military Aviation: Basic Physiology and Applied Perspectives

Abstract: Acute hypobaric hypoxia (HH) is a major physiological threat during high-altitude flight and operations. In military aviation, although hypoxia-related fatalities are rare, incidences are common and are likely underreported. Hypoxia is a reduction in oxygen availability, which can impair brain function and performance of operational and safety-critical tasks. HH occurs at high altitude, due to the reduction in atmospheric oxygen pressure. This physiological state is also partially simulated in normobaric envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 107 publications
2
50
0
Order By: Relevance
“…The findings of the current study support the hypotheses of the magnitude of hypoxia results in worsening cognition and vigilance ( McMorris et al, 2017 ; Pun et al, 2018 ; Shaw et al, 2021 ). Specifically, in the current study, MH resulted in greater PVT RT while SH exhibited greater PVT RT and PVT E compared to the Normoxia condition.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The findings of the current study support the hypotheses of the magnitude of hypoxia results in worsening cognition and vigilance ( McMorris et al, 2017 ; Pun et al, 2018 ; Shaw et al, 2021 ). Specifically, in the current study, MH resulted in greater PVT RT while SH exhibited greater PVT RT and PVT E compared to the Normoxia condition.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Pun et al (2018) reported that PVT RT was highly correlated to acute mountain sickness symptoms (r = 0.62) which suggested that acute hypoxia reduces cognitive processing speed and/or movement during vigilance tasks increasing the time to complete the task. It has been hypothesized that the magnitude and duration of hypoxia greatly influences cognitive and vigilance outcomes ( Pun et al, 2018 ; Shaw et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations